1968-1978 /quelques .../ acquisitions/ musée de grenoble. - Musée de Grenoble, Grenoble (Grenoble : Ville de Grenoble, 1979)
Adami, Valerio ; Agam, Yaacov ; Aillaud, Gilles ; Barrere, Jean-Claude ; Bertholin, Jean-Marie ; Bill, Max ; Bishop, James ; Brauner, Victor ; Cane, Louis ; Cruz-Diez, Carlos ; etc.
boek